Synthesis, characterization, and thermophysical properties of maghemite (γ-Fe2O3) nanofluids with and without magnetic fields effect / Irwan Nurdin - Irwan, Nurdin (2016)

(untitled)
Synthesis, characterization, and thermophysical properties of maghemite nanofluids have been studied with and without magnetic fields effect. The objectives of study are to synthesize maghemite nanoparticles and their characterization using various methods, to prepare stable maghemite nanofluids, and measurement of thermophysical properties of maghemite nanofluids with and without external magnetic fields effect. Maghemite nanoparticles were synthesized by chemical co-precipitation method with different concentrations of nitric acid. Maghemite nanofluids were then prepared and the stability of the nanofluids were characterized by zeta potential and dynamic light scattering at different pH and time of storage. Lastly, measurements of thermal conductivity, viscosity, and electrical conductivity of maghemite nanofluids were taken at various particle volume fraction, temperatures, with and without strengths of magnetic fields. Results show that spherical shape of superparamagnetic maghemite nanoparticles with good thermal and suspensions stability was successfully synthesized within the size range of 9.3 to 14.7 nm. The stability of maghemite nanofluids show that the suspensions remain stable at acidic condition with zeta potential value of 44.6 mV at pH 3.6 and at basic condition with zeta potential -46.2 mV at pH 10.5. The isoelectric point of the maghemite nanoparticles suspensions is obtained at pH 6.7. The maghemite nanofluids remains stable after eight months of storage. The thermal conductivity of maghemite nanofluids linearly increases with increasing of particle volume fraction, temperature, and magnetic fields strengths. The kinematic viscosity of maghemite nanofluids increases with increasing of particle volume fraction and magnetic fields and decrease with increasing of temperature. Electrical conductivity of maghemite nanofluids increases with increasing of particle volume fraction and temperature and no effect with magnetic fields.